Implementasi Model Discovery Learning Pada Pembelajaran Pendidikan Agama Hindu Dan Budi Pekerti Di Sma Negeri 1 Semarapura - Aprilia, Ni Nengah; Nanduq, Ferdinandus; Armini, Ida Ayu Adi (UHN IGB Sugriwa Denpasar, 2024)
The discovery learning model is discovery learning so that this learning model is useful for the world of education, even learning Hindu religious education and character. Based on initial observations of the application of the discovery learning learning model at the research location, it shows an increase in learning motivation and student active responses. The theories used are Skinner's behavioristic theory and Vygotsky's constructivist theory. The research subjects were the principal, deputy principal for curriculum, Hindu religious and character education teachers, students in class XI.9. Data collection methods are observation, in-depth interviews, literature study and document study. The collected data was analyzed using qualitative descriptive analysis methods. The results of the research show (1) The process of implementing the discovery learning model in learning Hindu religious education and character at SMA Negeri 1 Semarapura, namely: (1) Stimulation, (2) Problem Statement, (3) Data Collection, (4) Data Processing, (5) Verification, (6) Generalization. The evaluation stage is the presentation of hypotheses and individual assessment. (2) Obstacles and efforts in implementing the discovery learning model in learning Hindu religious education and character at SMA Negeri 1 Semarapura. Barriers include: (1) lack of efficient learning time. (2) Lack of teacher skills in creating learning media. Efforts include: (1) optimizing learning time. (2) increasing and training teacher professionalism. (3) The impact of implementing the discovery learning model on learning Hindu religious education and character at SMA Negeri 1 Semarapura, namely (1) impact on school image, (2) impact on teacher skills, (3) impact on student learning motivation, (4) impact on student learning outcomes, (5) impact on students' active responses.